Pengaruh Pemberdayaan Keluarga Penerima Manfaat Program Keluarga Harapan melalui Family Development Session - Elly Kuntjorowati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2018)
The purpose of this research is to know the influence of family development session (FDS) towards social welfare of beneficiary family (KPM) of Family Hope Program (PKH) especially in health, education, economy enhancement and child protection. PKH is a government program in alleviating poverty, and FDS is an empowerment program inherent in PKH, whereas this poverty alleviation program is saidby the World Bank to be very effective in alleviating poverty. TheÂ research used a quantitative method because it would make use of hypothesis test, with its analysis used t-Test. Data was collected by using questionnaires, structured interviews, observation and document review. The results of the research show that the null hypothesis which says that there is no effect of FDS empowerment on KPMs welfare in the education, health, economic and child protection aspects is wrong or rejected, and the alternative hypothesis which says that there is indeed an effect of FDS empowerment on health, education, economics and child protection is right or accepted. In brief, it can be said that FDS is very influential for the improvement of KPM. The conclusion is that the empowerment of FDS is necessary to be continued and enhanced because it is able to improve the familyâ€™s social welfare in the scope of education, health, economy and child protection, and it is suggested that non-cash assistance is to be continually accepted by KPM without any delay. It is recommended to Dayasos General Directorate to add the number of PKH assistants in each sub-district and to improve their related knowledge accordingly, because the PKH assistants function as the spearhead in implementing the program. It is better for each sub-district to be accompanied by more than one assistant after considering that there is a large number of KPMs. There is a must to train each assistant with FDS material and modules to support their performance in carrying out their task of the program.